2011
DOI: 10.1007/s12274-011-0139-4
|View full text |Cite
|
Sign up to set email alerts
|

Catalyst-free synthesis and shape control of CdTe nanowires

Abstract: The procedure reported here allows for the size and shape control of CdTe nanowires by means of colloidal chemistry. Thus, ultrathin, straight, saw-tooth-like and one-sided branched nanowires with zinc blende structures could be synthesized. Their formation does not require any catalyst and is most likely due to the oriented attachment of nanoparticles formed in the beginning of the reaction. The use of oleylamine as a solvent turned out to be crucial in order to achieve CdTe nanowires. The reaction between ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…S1, A and B) (16,17). Four atomic layers of Pt were then deposited on the surface of each Pd cube as a conformal shell ( fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S1, A and B) (16,17). Four atomic layers of Pt were then deposited on the surface of each Pd cube as a conformal shell ( fig.…”
mentioning
confidence: 99%
“…We prepared Pd@Pt 4-5L octahedra from Pd octahedra of 19.4 nm in edge length ( fig. S4) (16,20) and then etched away the Pd templates using more etchant relative to the standard procedure. The HAADF-STEM image in Fig.…”
mentioning
confidence: 99%
“…In the previous section we discussed the temperature and growth time influence on the shape of CIS NPs ( Figure 2) and showed that CIS NPs with different shapes (Figure 3) are observed due to certain combinations of precursors, surfactants, and solvents. They may act not only as capping, but also as activation agents, [39,40] and, thus, influence both the nucleation and the growth stage of the synthesis. Just a few reports describe the underlying mechanisms of shape control, in particular the ligand protection strategy.…”
Section: Shape Control Of Cuinse 2 Nps Through the Ligand-protection mentioning
confidence: 99%
“…[15,38] Ligands have manifold functions in the synthesis of nanomaterials. They may act not only as capping, but also as activation agents, [39,40] and, thus, influence both the nucleation and the growth stage of the synthesis. [41] Ligands react with the precursors and lower their activity; this results in a delay of the nucleation process, particularly in the presence of strong binding ligands.…”
Section: Shape Control Of Cuinse 2 Nps Through the Ligand-protection mentioning
confidence: 99%
“…Поэтому автокаталитический синтез ННК CdTe безусловно обладает рядом преимуществ. Исследования автокаталитического синтеза ННК CdTe представлены слабо: в работах [15][16][17][18][19][20] показана возможность формирования наноразмерных столбиков при гальваническом и/или гидротермальном осаждении на подложки с ингибиторным слоем. Однако указан-Рис.…”
Section: Introductionunclassified